A PERFORMANCE ANALYSIS OF REGIONAL BUDGET OF JAYAWIJAYA REGENCY FROM 2010 TO 2014 - Didi Yigibalom; Ida Ayu Purba Riani (Universitas Cenderawasih, 2016)
This study aims to assess performance of Regional Budget (APBD) which includes revenues, spending/expenditures and financing activities of Jayawijaya Government. The data used was the budgeted and realization of Revenue, Spending/Expenditure and Financing activities of Jayawijaya regency from 2010 to 2014. The analysis techniques used was a qualitative approach through various financial ratios. To calculate revenues performance this study employed Variant Analysis (differences of) Budget Revenue, Revenue Growth, Degree of Independence of the region, Regional Reliance to the central government, Degree of Decentralization, Local Tax Effectiveness and Overlay analysis to measure performance of the generated income. Meanwhile to measure expenditure used Variant Analysis (difference) Budgeted Expenditure, Growth of Regional Expenditure, Synchronization of Governmental Spending, Spending Effectiveness and Overlay analysis to measure overall spending/expenditures performance. Following the analysed data, the study obtained following results: 1) Jayawijaya’s revenue performance during 2010 to 2014 based on the overlay analysis was not good. The main caused was due to low degree of the region financial independence, high degree of fiscal dependence for external funding as well as the low degree of fiscal decentralization, 2) Spending/Expenditure Performance of Jayawijaya from 2010 to 2014 was good. This was because of the increasing growth of Jayawijaya’s spending/expenditure and the effectiveness of spending/expenditure in Jayawijaya. Keywords: Budget, Revenue, Spending/ Expenditure, Regional Budget Performance